Does Democracy Enhance Health? New Empirical Evidence 1900-2012 - Wang, Yi-ting; Mechkova, Valeriya; Andersson, Frida (Political research quarterly, 2019)
This study tests the relationship between democracy and population health. Some studies argue that democracies are more likely than authoritarian regimes to provide public goods and, thus, enhance health. However, recent research has challenged this argument and identified good governance as the crucial determinant of human development. Using a newly collected dataset covering 173 countries from 1900 to 2012, our analyses show that across models with various specifications, democratic elections have consistent effects on health outcomes even when other important factors, including good governance, are taken into account. There are some nuances in this relationship. First, the impact of electoral democracy tends to persist over time. Furthermore, the positive effects are particularly salient once the quality of elections has achieved a certain threshold. Our results also suggest that previous studies yielded mixed results in part because the commonly used governance indicators are only available for relatively short time periods, and the sample does not reflect the entire range of variation in measures of both democracy and governance.